12. Online Polling Services - Baggaley, Jon; Kane, Tom; Wade, Bill (International Review of Research in Open and Distributed Learning, 2002)
Real-time collection of student opinions and their instant feedback can be useful in guiding the design and implementation of online educational sessions. Students can gain insights into each others’ attitudes and opinions, often anonymously and confidentially; and teachers can adapt to the feedback in directing the progress of a session based on, in effect, a series of “if then” contingency measures. Online tabular and diagrammatic features can provide useful visual summaries of polling results, indicating whether or not the session’s learning outcomes are being achieved. Online polling services available differ greatly in the extent to which they provide these useful educational features. To guide distance educators in their selection and implementation of online polling and quizzing procedures, an evaluation study was conducted featuring a selection of the poll creation systems that were available at the time of study.All questionnaire, quizzing, survey, and assessment products/ services are referred to generically in the report as “polling systems.”